Effect of land use and environmental variables on phytoplankton community structure in high-elevation river, upper Yangtze river, China - Wang, Zunyan; Li, Qi; Tian, Yulu; Li, Xi; Chen, Xingyu; Tian, Yu; Xue, Jie (Frontiers in Environmental Science, 2023)
The Qinghai-Tibet Plateau is an ecologically fragile region. The changes in physicochemical parameters of water quality [PPOWQ] and land use types [LUT] in different regions will affect the phytoplankton community in rivers, thus threatening the ecosystem. Taking the phytoplankton community as an indicator variable, it is of great significance to study the relative influence of symbiotic factors on regulating human activities and river ecological protection. The results showed that the proportions of Bacillariophyta, Cyanophyta, and Chlorophyta were >84% in the phytoplankton community of taxa composition. The abundance of the phytoplankton community varied from 1.47×105 to 7.58×105 cells/L. Bacillariophyta had the highest average abundance (>82%). The results of the variance partitioning analysis showed that PPOWQ was the main variable affecting the changes in the phytoplankton community. Redundancy analysis showed that local factors (total nitrogen, salinity, water temperature) and regional factors (forestland, grassland, unused land) (P<0.05) were the main factors causing the changes in community structure and abundance of dominant algae. The analysis of structural equation models showed that LUT had the least direct impact on the abundance of the phytoplankton community, mainly through changing nutrients and physical parameters. Water temperature and nutrients are still the main factors affecting phytoplankton community abundance. Farmland and forestland are the main sources of total nitrogen and total phosphorus in rivers. In general, in the ecologically vulnerable area, it is of guiding significance for the ecological monitoring and management of plateau rivers. In addition to considering water quality, it is also necessary to reasonably plan the LUT around rivers.